Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 10 - Section 10.5 - Finding Factors of Special Products - Exercise - Page 354: 36



Work Step by Step

This is a perfect square trinomial in the following manner $$ -2y^2+12y-18=-2(y^2-6y+9)=-2(y-3)(y-3) .$$ One can check as follows $$ -2(y-3)(y-3)= -2(y^2-3y-3y+9)= -2(y^2-6y+9)=-2y^2+12y-18 .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.